Osteoarthritis as a clinical marker of cardiovascular-kidney-metabolic multimorbidity: a population-based cohort study in China - Zou, Yue; Zhang, Yanyan; Sun, Xiujiang; Zhao, Wenbo; Zhang, Guodong (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular-kidney-metabolic (CKM) multimorbidity is increasingly recognized as a major global health concern. Although osteoarthritis (OA) is traditionally viewed as a degenerative joint condition, recent evidence suggests it may reflect systemic inflammation and metabolic dysfunction. However, its role as a potential clinical marker of CKM multimorbidity remains unclear.MethodsThis population-based cohort study included 1,842 participants with osteoarthritis from a community registry in China. CKM multimorbidity was defined as the sequential development of cardiovascular disease (CVD), chronic kidney disease (CKD), and type 2 diabetes mellitus (T2DM). Participants were followed for incident CKM events. Logistic regression models estimated odds ratios (ORs) for new-onset, double, and triple CKM outcomes. A multi-state model was applied to assess progression trajectories between disease stages.ResultsOver the study period, 32.6% of participants developed at least one CKM condition, 27.1% progressed to double CKM, and 5.4% developed triple CKM. Higher osteoarthritis burden was associated with increased risk of CKM multimorbidity. Adjusted ORs (95% CI) for new-onset, double, and triple CKM were 2.64 (2.33 – 3.00), 2.40 (2.11 – 2.72), and 1.49 (1.21 – 1.84), respectively. Multi-state modeling confirmed that osteoarthritis.ConclusionOsteoarthritis is strongly associated with the onset and progression of CKM multimorbidity. As a clinically observable and common condition, OA may serve as an early indicator for identifying individuals at heightened risk of multi-organ metabolic decline. These findings support the integration of OA status into risk stratification frameworks for CKM disease prevention and management.